Utilização de técnicas multivariadas e moleculares na caracterização e seleção de genótiopos de feijão-caupi de porte ereto e ciclo precoce. - Dias, Francisco Tiago Cunha (2009)
Cowpea has great socioeconomic importance in relation to their high contents of protein, drought resistance and good yield. Being cultivated in tropical and subtropical regions of Africa, Brazil and Asia, cowpea is cultivated predominantly by small farmers who use few technological resources. In recent years, cowpea has drawn the attention of medium and large farmers, which require cultivars suited to mechanization, early and responsive to environmental improvements. To start a breeding program that meets the needs of these new cowpea cultivars become necessary the knowledge of the germplasm available, and the relationship between variables related to yield and techniques appropriate to the selection of cowpea. In this context, this study aimed to evaluate the genetic divergence of erect and early cowpea genotypes through phenotypic and molecular characters, besides to study the interrelations among traits related to yield and the selection index appropriate to indentify the best erect and early cowpea genotypes. For the assessment of genetic diversity by molecular markers, there were extractions of DNA from 46 genotypes from the Germplasm Bank of the Universidade Federal do Ceará and Embrapa Meio Norte and then PCR was performed with eight ISSR primers in the Laboratory of Molecular Biology of Embrapa Agroindústria Tropical. For the analysis of genetic divergence of phenotypic markers, study of canonical correlation, analysis and application to track the index of selection was carried out an experiment in randomized blocks with four replicates and 28 genotypes in Fazenda Lavoura Seca, which belongs to the Centro de Ciências Agrárias Universidade Federal do Ceará (CCA / UFC), located in Quixadá, Ceará. From the results obtained by molecular markers it was found that these were effective in identifying the polymorphism in erect and early cowpea genotypes. There is a tendency for grouping of genotypes according to the origin. Assessing the genetic divergence in phenotypic markers showed that CE-46 genotype is the most divergent among the 28 genotypes. Crossings between the groups VIII and XI and groups VII and VIII may result in favorable gene combinations and response variables initial flowering of the crop cycle and contribute to greater magnitude to the quantification of genetic divergence among the genotypes. From studies using canonical correlation and path analysis it is concluded that direct selection based on the seed number per pod and one hundred seed weight favors the increase in yield cowpea. A direct selection based on the number of pods per plant tends to decrease the cycle in cowpea, the decrease in the pod length and the increase in the seed number per pod contribute to the increase in cowpea yield. The base and multiplicative selection indices are more efficient in the erect and early cowpea genotypes selection . The CE-113 and CE-748 genotypes combine, simultaneously, several favorable morphological and agronomic characters besides the high yield.